2005
DOI: 10.1080/09603120500105935
|View full text |Cite
|
Sign up to set email alerts
|

Environment, wealth, inequality and the burden of disease in the Accra metropolitan area, Ghana

Abstract: The study examines environmental problems and adverse impacts on the health of urban households in the Accra metropolitan area, Ghana. Accra is faced with severe inadequacy of urban infrastructure in the face of rapid population growth in the metropolis. More than half of the city's population do not have access to solid waste collection services. Only 39.8% of households have indoor pipe and over 35.0% of households depend on unsanitary public latrines whilst 2.5% do not have access to toilet facilities. Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 9 publications
1
37
0
Order By: Relevance
“…Generally, a chronic problem confronting all sub-Sahara African cities including Accra in Ghana is a proliferation of squatter and informal settlements, peripheral sprawl, and central city tenements, all lacking basic infrastructure services with poor sanitation (Boadi and Kuitunen, 2005;Nuno-amarteifio, 1995;Bannerman, 2000;Wurapa, 1973;Makoni et al, 2004;Mabogunje, 1995;Satterthwaite, 1993;Von Schirnding, 1996). Indeed, cities in this region are not only rapidly urbanizing, but the urban environments here are fast deteriorating and this kind of urban growth phenomenon may better be described as 'ruralization'' than ''urbanization'' (Bannerman, 2000;Makoni et al, 2004;Mabogunje, 1995;Von Schirnding, 1996;Taiwo, 1996;Majani, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Generally, a chronic problem confronting all sub-Sahara African cities including Accra in Ghana is a proliferation of squatter and informal settlements, peripheral sprawl, and central city tenements, all lacking basic infrastructure services with poor sanitation (Boadi and Kuitunen, 2005;Nuno-amarteifio, 1995;Bannerman, 2000;Wurapa, 1973;Makoni et al, 2004;Mabogunje, 1995;Satterthwaite, 1993;Von Schirnding, 1996). Indeed, cities in this region are not only rapidly urbanizing, but the urban environments here are fast deteriorating and this kind of urban growth phenomenon may better be described as 'ruralization'' than ''urbanization'' (Bannerman, 2000;Makoni et al, 2004;Mabogunje, 1995;Von Schirnding, 1996;Taiwo, 1996;Majani, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…This leads to poor waste management practices which severely compromises air quality in these areas. Studies conducted in Accra, Ghana reported that, majority of households in the city manage their solid waste by openly burning the garbage (Boadi and Kuitunen, 2005;Amegah et al, 2012;Zhou et al, 2014). The combustion activities releases dioxins, furans and other air pollutants which severely impacts household and local air quality.…”
Section: Ensuring Sound Waste Management Practicesmentioning
confidence: 97%
“…This risks impact particularly the poorest people in developing nations where the very young and very old are the principal groups affected [11,12,18,29,30,56]. Intervention strategies have centred on traditional engineered barriers to the faecal-oral route of infection [5,9,22,23] and some work has been reported on their cost-effectiveness [16][17][18].…”
Section: Some Preliminariesmentioning
confidence: 99%